Identifying and Analyzing Factors Influencing Urban Decline (Case Study: The Border City of Zabol) - Rakhshani Nasab, Hasan Ali; Jahan Bin, Nima (Management Strategies and Engineering Sciences, 2023)
Cities, as living entities, lose their cultural, social, economic, and physical vitality if urban decline persists, leading to increased risks of both natural and human-made hazards. Given the existential impacts and the role of this phenomenon in urban life degradation, instability, and threats to urban livability, addressing this issue becomes crucial. This study aims to identify and analyze the factors influencing urban decline. The research is mixed-method in nature and falls within the category of sequential-exploratory studies. Initially, qualitative data were collected, followed by quantitative data in the second phase, culminating in an integrated analysis of both. Due to the methodological integration, meta-synthesis was used in the first (qualitative) phase to develop a conceptual model of urban decline (explaining its components), while a survey method was employed in the second (quantitative) phase to explore the interrelationships among the components of decline in the border city of Zabol. Key components of the conceptual model include political factors, urban governance, environmental factors, economic factors, and socio-cultural factors. To operationalize the conceptual model and uncover causal relationships, a researcher-developed questionnaire aligned with the findings of the first phase was utilized. The statistical population consisted of managers and decision-makers in urban affairs as well as residents of Zabol. The sample size, determined using Cochran’s formula with a 0.05 margin of error, was calculated to be 383 participants. The results support all identified components contributing to the phenomenon, with political issues identified as the most influential factor driving urban decline in Zabol.